Pharmacokinetics of florfenicol and its metabolite, florfenicol amine, in rice field eel (Monopterus albus) after a single‐dose intramuscular or oral administration. Issue 3 (22nd May 2012) - XIE, L.‐L.; WU, Z.‐X.; CHEN, X.‐X.; LI, Q.; YUAN, J.; LIU, H.; YANG, Y.
<x xml:space="preserve">Abstract</x> The pharmacokinetics of florfenicol (FF) and its metabolite, florfenicol amine (FFA), were studied in rice field eel (Monopterus albus) after a single dose (20 mg/kg) by intramuscular (i.m.) or oral gavage (p.o.) dose at 25 °C. The elimination half‐lives (t1/2β), peak concentration of FF (Cmax), and time to reach FF peak concentration (Tmax) in plasma were estimated as 18.39 h, 10.83 μg/mL, and 7.00 h, respectively, after i.m. injection and 13.46 h, 8.37 μg/mL, and 5 h, respectively, after p.o. administration. The Tmax values of FF in tissues (i.e., kidney, muscle, and liver) were larger for i.m. injection compared with those for p.o. administration. The t1/2β had the following order kidney > muscle > liver for i.m. administrated and kidney > liver > muscle for p.o. administrated. The largest area under the concentration–time curve (AUC) was calculated to be 384.29 mg · h/kg after i.m. dosing, and the mean residence time (MRT) was 42.46 h by oral administration in kidney. FFA was also found in all tissues with a lower concentration than FF for both i.m. and p.o. administrations throughout the study. The elimination of FFA was slow with a t1/2β between 18.19 and 47.80 h in plasma and tissues. The mean metabolic rate of FFA for i.m. and p.o. administrations was >23.30%.